Accuracy of computer programs in predicting orthognathic surgery hard tissue response. - Kaipatur N; Al-Thomali Y; Flores-Mir C (Journal of Oral & Maxillofacial Surgery (02782391), 2009)
PURPOSE: The aim of this systematic review was to investigate the accuracy of computer programs in predicting skeletal changes after orthognathic surgery. MATERIALS AND METHODS: A systematic computerized database search was conducted with the help of a health sciences librarian. Specific selection criteria were used to select articles, reference lists of the selected articles were also searched for any potential articles that might have been missed in the electronic search, and additional information not available through the articles was obtained directly from the corresponding author. RESULTS: Of the 79 initially identified articles (abstracts/titles), only 9 fulfilled the final selection criteria. As expected, no dental changes occurred but the computer programs were unable to precisely predict all the skeletal changes. Most of the prediction inaccuracies were within 2 mm or 2 degrees , which can be partially attributed to measurement errors in cephalometric tracing. CONCLUSIONS: This systematic review showed that computer programs cannot consistently predict the skeletal changes occurring after orthognathic surgery but their results may be considered inside a clinically acceptable range. Last-minute changes by the surgeons could also explain the differences. We also conclude that no software program was shown to be superior in prediction accuracy compared with its competitor. Copyright © 2009 by the American Association of Oral and Maxillofacial Surgeons.